Examining Social Justice Implications of Proctoring Technologies in Online Assessments within Open and Distance e-Learning (ODeL) Environments: Privacy, Equity, and Access - Cele, Siyanda; Maphalala, Mncedisi Christian (Universitas Majalengka, 2025)
The study explores the social justice implications of proctoring technologies in online assessments within Open and Distance e-learning (ODeL) environments, focusing on privacy, equity, and access. Through a systematic literature review (SLR) adhering to PRISMA protocols, the study analyses peer-reviewed empirical research published between 2014 and 2024. Key thematic areas identified include the ethical concerns surrounding privacy and surveillance, the impact of proctoring technologies on equitable access to assessments, and the potential biases embedded within automated monitoring systems. The study highlights the need for fair and transparent strategies for online proctoring in Open and Distance e-Learning (ODeL) environments. It is essential to balance maintaining academic integrity and respecting students' privacy and ethical concerns. Proctoring technologies should align with Social Justice Theory to safeguard students' rights to privacy, equal access, and active participation. Future studies should focus on developing policies and technologies that enhance fairness and trust while protecting students' rights during online assessments.